12a-3d ÷ 12a+3d при a= - 3/4 d= -5/6 уравнение 2x - 12 (3-x)= 1+3 (x+2) 16+5 (-c-2 (c-4)) = 12 (3-2c)-1 13b-(9b-(8b-(6- =

Solomina2 Solomina2    2   06.09.2019 02:00    0

Ответы
imrangaraev imrangaraev  06.10.2020 20:25
Это на 1 и 2.. Надеюсь, что все верно
12a-3d ÷ 12a+3d при a= - 3/4 d= -5/6 уравнение 2x - 12 (3-x)= 1+3 (x+2) 16+5 (-c-2 (c-4)) = 12 (3-2c
12a-3d ÷ 12a+3d при a= - 3/4 d= -5/6 уравнение 2x - 12 (3-x)= 1+3 (x+2) 16+5 (-c-2 (c-4)) = 12 (3-2c
ПОКАЗАТЬ ОТВЕТЫ
LaMihaLa LaMihaLa  06.10.2020 20:25
Решение задания смотри на фотографии его
12a-3d ÷ 12a+3d при a= - 3/4 d= -5/6 уравнение 2x - 12 (3-x)= 1+3 (x+2) 16+5 (-c-2 (c-4)) = 12 (3-2c
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра